DbPTM in 2022: an updated database for exploring regulatory networks and functional associations of protein post-translational modifications. Issue Volume 50:Issue D1(2022) (12th November 2021) - Li, Zhongyan; Li, Shangfu; Luo, Mengqi; Jhong, Jhih-Hua; Li, Wenshuo; Yao, Lantian; Pang, Yuxuan; Wang, Zhuo; Wang, Rulan; Ma, Renfei; Yu, Jinhan; Huang, Yuqi; et al.
Abstract: Protein post-translational modifications (PTMs) play an important role in different cellular processes. In view of the importance of PTMs in cellular functions and the massive data accumulated by the rapid development of mass spectrometry (MS)-based proteomics, this paper presents an update of dbPTM with over 2 777 000 PTM substrate sites obtained from existing databases and manual curation of literature, of which more than 2 235 000 entries are experimentally verified. This update has manually curated over 42 new modification types that were not included in the previous version. Due to the increasing number of studies on the mechanism of PTMs in the past few years, a great deal of upstream regulatory proteins of PTM substrate sites have been revealed. The updated dbPTM thus collates regulatory information from databases and literature, and merges them into a protein-protein interaction network. To enhance the understanding of the association between PTMs and molecular functions/cellular processes, the functional annotations of PTMs are curated and integrated into the database. In addition, the existing PTM-related resources, including annotation databases and prediction tools are also renewed. Overall, in this update, we would like to provide users with the most abundant data and comprehensive annotations on PTMs of proteins. The updated dbPTM is now freely accessible at https://awi.cuhk.edu.cn/dbPTM/ .